The Influence of Fundamental, Technical and Inflation Factors on Stock Prices in Food and Beverages Companies Listed on IDX - Siti Dini; Amelia Amelia; Ramelda Veronika Br. Hutabarat; Pangeran Amansyah Pasaribu (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to determine whether technical and fundamental analysis have a partial or simultaneous influence on stock prices. The population of this study amounted to 25 companies listed on the Indonesia Stock Exchange. In sampling, the researcher coordinates the objectives of the sampling method and takes the sample by considering several criteria. In this study, the data used are the company's financial statements obtained from the website www.idx.co.id and the official website from the company itself. The researcher uses descriptive analysis method and multiple linear regression analysis in his research. The results of this study partially show that Dividend Per Share has an effect and is significant on stock prices, Earning Per Share has an effect and is significant on stock prices, Trading Volume has no and no significant effect on stock prices, and Inflation has no significant effect on stock prices. Simultaneously, Dividend Per Share, Earning Per Share, Trading Volume and Inflation have a significant effect on stock prices.